(untitled) (Педагогіка вищої та середньої школи, 2010)
The article deals with the problem concerning the role of group work in the process of schoolchildren learning. Group work in school didactics is considered to be a universal organizational form of educational process in modem schools. Scholars’ and pedagogues’ research on group work is supported by teachers in process of learning at school. However, a number of shortages of experimental checks on introduction of the forms of group work in educational process have caused numeral researches devoted to this problem.